2007
DOI: 10.1093/rheumatology/kem186
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin therapy improves endothelial-dependent vasodilation in patients with systemic lupus erythematosus: an 8 weeks controlled trial

Abstract: Introduction. Patients with systemic lupus erythematosus (SLE) have recognized reduction in endothelium-dependent vasodilation. Evidence demonstrates that statins are able to improve endothelial function independently on their hypolipemic action. Objectives. To evaluate the efficacy of atorvastatin in improving vasodilation in SLE patients with and without conventional risk factors for coronary heart disease (CHD). Patients and methods. Sixty-four SLE women, mean age 31 AE 8 yrs, received atorvastatin 20 mg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 43 publications
0
66
0
1
Order By: Relevance
“…Another statin, simvastatin, led to a similar reduction in disease activity in female patients [15]. A 1-year trial with atorvastatin demonstrated a decrease in cholesterol levels, proteinuria, and rate of progression of chronic kidney disease in patients with SLE with LN [16]. TNF-α has been shown to be a potential target in the treatment of SLE, and there is a role for the HMG-CoA reductase inhibitor simvastatin [17].…”
Section: Role Of Statins In Cardiovascular Diseasementioning
confidence: 99%
“…Another statin, simvastatin, led to a similar reduction in disease activity in female patients [15]. A 1-year trial with atorvastatin demonstrated a decrease in cholesterol levels, proteinuria, and rate of progression of chronic kidney disease in patients with SLE with LN [16]. TNF-α has been shown to be a potential target in the treatment of SLE, and there is a role for the HMG-CoA reductase inhibitor simvastatin [17].…”
Section: Role Of Statins In Cardiovascular Diseasementioning
confidence: 99%
“…However, the available data from that study are preliminary and have been presented only in abstract form; a full report is awaited. In a short-term study of patients with SLE, atorvastatin improved endothelium-dependent vasodilatation independently of the presence of conventional risk factors (12), indicating that atorvastatin may be useful in preventing atherosclerotic cardiovascular complications in this clinical setting.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies show that statins can also interfere with Th1/Th2 balance as well as MHC class II expression, which can lead to changes in immune responsiveness (11,(17)(18)(19). In this regard, many studies evaluated the effects of this drug on various immunologic-related conditions such as rheumatologic diseases (20)(21)(22)(23), response to different vaccines (12,14,24), central nervous system autoimmune diseases (25)(26)(27), and chronic obstructive pulmonary disease (28).…”
Section: Discussionmentioning
confidence: 99%